Collaborative Learning and Emergency Remote Teaching in Interpreter Training: Teachers' and Students' Experiences During COVID-19 - Castillo-Chumpitaz, Karolayn Angelica (2022)
Mandatory social distancing due to COVID-19 presented the challenge of shifting on-site education to virtual learning environments in order to resume lessons in universities around the world. In this context, Universidad Peruana de Ciencias Aplicadas (UPC) had to shift its Educational Model to Emergency Remote Teaching (ERT). This study aims to analyze Collaborative Learning in the process of adapting the virtual learning environment (VLE) used in the four Interpreter Training courses belonging to UPC's undergraduate program in Professional Translation and Interpretation (TIP) during the two academic terms of ERT in 2020. Six interpreter trainers were interviewed to explore their perspectives on adapting the VLE to allow and promote Collaborative Learning in their classes during ERT, while eleven interpreting students shared their perceptions on this VLE's effectiveness in a focus group. Results show how Collaborative Learning was developed through bonds of Positive Interdependence and Promotive Interaction between members of the learning community, both teachers and students.